Dual action of polarised zinc hydroxyapatite - guar gum composite as a next generation bone filler material. (2022) - Swain, Subhasmita; Mishra, Sapna; Patra, Abhishek; Praharaj, Rinmayee; Rautray, Tapash
Abstract: Implantable filler materials modified with Zn is a growing trend in the engineering of biomaterials for improvement of bone regeneration. Hydroxyapatite is used as a vital component in biocomposites and surgical implant coating. The purpose of this experiment was to synthesize Zn 2+ substituted hydroxyapatite to obtain a final composite of Guar gum- zinc substituted hydroxyapatite (ZnHA-GG) composites and the development of surface negative charge on ZnHA-GG composite was carried out using a Corona Poling unit and the assessment of biocompatibility and antibacterial activity were carried out. In vitro culture of MG-63 osteoblast cells and S. aureus bacterial cells were then carried out on polarized composites in conjunction with non-polarized composites to find the effects of polarization on adhesion of cells, osteogenic differentiation as well as antibacterial efficacy. It was inferred that incorporation of Zn 2+ ions into composites of Guar Gum hydroxyapatite structure increased the osteoblasts spreading, boosts antibacterial activity on the composite surface, and amplifies RUNX2, osteocalcin, type I collagen formulation by osteoblasts.